Methodological issues in family expatriation studies and future directions - Goede, Julia; Holtbrügge, Dirk (International Studies of Management and Organization, 2021)
As scholars uncovered the crucial role of the family in the relocation of organization-assigned expatriates, the investigation of the expatriate's family became of interest to management researchers and practitioners alike. While recently the number of studies evaluating the family interface of international assignments has risen significantly, the topic remains at an emerging stage. In order to support the future development of trustworthy and credible empirical research, this article examines the research methodology and the associated issues of the extant literature. To investigate the family expatriation topic, we included articles by pre-defined criteria with a management focus from the international business, (international) human resource, as well as management and psychology disciplines. By critically assessing how research has been conducted in family expatriation studies, we provide a foundation from which future studies can infer the appropriate choice and application of research methods. In order to achieve this objective, we discuss the research methodology of 69 published articles, identify methodological issues, and offer recommendations.
CRIS-Team WoS Importer:2021-07-16
Keywords: Gender